Dental health assessed using panoramic radiograph and adverse events in chronic kidney disease stage 4-5 patients transitioning to dialysis and transplantation-A prospective cohort study - Järvisalo Mikko J.; Jokihaka Viljami; Hakamäki Markus; Lankinen Roosa; Helin Heidi; Koivuviita Niina S.; Hellman Tapio; Metsärinne Kaj (Public Library of Science, 2022)
Background and aims
Oral health could potentially be a modifiable risk factor for adverse outcomes in chronic kidney disease (CKD) patients transitioning from predialysis treatment to maintenance dialysis and transplantation. We aimed to study the association between an index of radiographically assessed oral health, Panoramic Tomographic Index (PTI), and cardiovascular and all-cause mortality, major adverse cardiovascular events (MACEs) and episodes of bacteremia and laboratory measurements during a three-year prospective follow-up in CKD stage 4–5 patients not on maintenance dialysis at baseline.
Methods
Altogether 190 CKD stage 4–5 patients without maintenance dialysis attended panoramic dental radiographs in the beginning of the study. The patients were followed up for three years or until death. MACEs and episodes of bacteremia were recorded during follow-up. Laboratory sampling for C-reactive protein and leukocytes was repeated tri-monthly.
Results
PTI was not associated with baseline laboratory parameters or C-reactive protein or leukocytes examined as repeated measures through the 3-year follow-up. During follow-up, 22 patients had at least one episode of bacteremia, but only 2 of the bacteremias were considered to be of oral origin. PTI was not associated with incident bacteremia during follow-up. Thirty-six patients died during follow-up including 17 patients due to cardiovascular causes. During follow-up 42 patients were observed with a MACE. PTI was independently associated with all-cause (HR 1.074 95% CI 1.029–1.122, p = 0.001) and cardiovascular (HR 1.105, 95% CI 1.057–1.157, p<0.0001) mortality, as well as, incident MACEs (HR 1.071 95% CI 1.031–1.113, p = 0.0004) in the multivariable Cox models adjusted for age and kidney transplantation or CKD treatment modality during follow-up.
Conclusions
Radiographically assessed dental health is independently associated with all-cause and cardiovascular mortality and MACEs but not with the incidence of bacteremia in CKD stage 4–5 patients transitioning to maintenance dialysis and renal transplantation during follow-up.